The Study of Exchange Equilibrium and the Beginning of the Theory of Social Equilibrium in Economic Texts by Pareto - Андрей Анатольевич Зотов (Journal of Economic Sociology, 2010)
In order to understand systematically the meaning of the sociological text of Vilfredo Pareto it is necessary to have an idea of the peculiarities of economic stage of his scientific work and his research field. The paper deals with the impact of economic stage on the sociological papers of this scientist, particularly on the development of the theory of social equilibrium. The reasons for his transferring to political economy are also under paper analysis.